Mitigation of graphene oxide toxicity in C. elegans after chemical degradation with sodium hypochlorite. (September 2021) - Bortolozzo, Leandro S.; Côa, Francine; Khan, Latif U.; Medeiros, Aline M.Z.; Da Silva, Gabriela H.; Delite, Fabricio S.; Strauss, Mathias; Martinez, Diego Stéfani T.
Abstract: Graphene oxide (GO) is a promising and strategic carbon-based nanomaterial for innovative and disruptive technologies. It is therefore essential to address its environmental health and safety aspects. In this work, we evaluated the chemical degradation of graphene oxide by sodium hypochlorite (NaClO, bleach water) and its consequences over toxicity, on the nematode Caenorhabditis elegans. The morphological, chemical, and structural properties of GO and its degraded product, termed NaClO-GO, were characterized, exploring an integrated approach. After the chemical degradation of GO at room temperature, its flake size was reduced from 156 to 29 nm, while NaClO-GO showed changes in UV–vis absorption, and an increase in the amount of oxygenated surface groups, which dramatically improved its colloidal stability in moderately hard reconstituted water (EPA medium). Acute and chronic exposure endpoints (survival, growth, fertility, and reproduction) were monitored to evaluate material toxicities. NaClO-GO presented lower toxicity at all endpoints. For example, an increase of over 100% in nematode survival was verified for the degraded material when compared to GO at 10 mg L −1 . Additionally, enhanced dark-field hyperspectral microscopy confirmed the oral uptake of both materials by C. elegans . Finally, this work represents a new contribution toward a better understanding of the links between the transformation of graphene-based materials and nanotoxicity effects (mitigation), which is mandatory for the safety improvements that are required to maximize nanotechnological benefits to society. Graphical abstract: Image 1 Highlights: Sodium hypochlorite is effective for graphene oxide (GO) chemical degradation. Toxicity of GO on C. elegans was mitigated after degradation. GO and its degraded material were internalized in C. elegans (oral uptake). C. elegans is a promising model for toxicity evaluation of GO by-products.